Makna Pernikahan dalam Perspektif Tasawuf - Lisnawati, Lisnawati; Imran, Zulfi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This articlediscusses the views of sufism on marriage. Marrriage between men and women and uniting to live to gogether as husband and wife in bondage. In terms, marriage Marriage is a contract that legalizes association between a man and woman who are not mahram. From that contract also, appear rights and obligations that must be fulfilled by each partner. marriage is one of the characteristics of human since they were first created. Allah did not create prophet Adam alaihissalam unless he also created Hawwa as his life partner. The nature of marriage is one of the caracteristics of humans since the first time Allah SWT created it. Where he made hawwa from the rib of the prophet Adam AS for them to become husband and wife in marriage. Then from both of them was born the entire human race with his permission. Because marriage is guarantee for the continuity of human civilization on earth. Mariage is also a way to get closer to allah swt. Therefore, the essence of mariage in the view of sufisim is one way to allah and draw closer to him. a skinah, mawaddah, and warohmah mariage will be achieeved. In order to build a marriage law with a tasawuf approach, it is necessary to connect the values of tasawuf with the law within the framework of benefit. For this reason, sufism values such us warak and zuhud as well as qonaah and so on need to bee developed and itegrated in a connected manner into marriage law. Marriage is an inner and outer bond between two people of different sexes (male and female) to live together in one household with the expectation of offspring based on islamic sharia provisions. It is hoped that by understanding the importance of marriage, it will provide a peaceful household life for every husband and wife.